The Notions of "Schemata" and "Schemas" in the Study of Literary Fictions - Vinagradovas, Michailas (Respectus Philologicus, 2002)
Schema theory in contemporary cognitive psychology (R. P. Abelson, D. E. Rumelhart, R. C. Schank) and artificial intelligence (M. Minsky, C. J. Fillmore, T. Winograd) deals with the organization of human knowledge. 'Image schema', introduced and developed in cognitive semantics (M. Johnson, G. Lakoff, M. Turner), is practically a cognitive tool based on metaphorization whereby features of a source cognitive domain (vehicle) are mapped onto a target cognitive domain (tenor) to present complex entities in terms of simpler ones. The relation between 'schema theory' and 'image schema' is that of hyponymy: the former is the superordinate while the latter is a hyponym since 'image schema' is only one of the possible species of Schank's Thematic Organization Points. Thus the difference in the plural forms of 'schema theory' and 'image schema', 'schemata' and 'schemas' respectively, reflects the difference between these notions. G. Cook's notion of 'schema refreshment' through discourse deviation is considered as the pivotal property of literariness. 'Schema refreshment' is grounded on metaphorization: evoking novel relationships between conflicting schemata in literary texts and discourse deviation leads to reconceptualization of the actual world. Cook's notion of 'schema reinforcement', when discourse deviation does not engender deviations in background assumptions, helps to understand better the 'incompleteness' (L. Doležel) of fictional worlds in literary texts. 'Schema reinforcement' may involve metaphorization, but it is usually of the 'image schema' type. The 'schema theory' approach also shows that the construction of new worlds in literary texts is based not on various kinds of similarities among different schemata but on the substitution of a schema for a completely new one. In sum, the contemporary notion of schema, which is not only the product of cross-fertilization of different academic disciplines but also of intercultural character, can be usefully applied to literary studies, especially in the analysis of the epistemological and ontological entities of fictional worlds created by literary texts.
Keywords: associative / Gestalt psychology; background / prior knowledge; cognition; fictional / new world; image schema; knowledge structure; inguistic deviation / patterning